MACHINE LEARNING PENDETEKSI WAJAH DENGAN OPEN CV MENGGUNAKAN PYTHON - Sunarsan Sitohang; Hotma Pangaribuan (LPPM Universitas Putera Batam, 2026)
Machine learning is a branch of artificial intelligence that enables computers to identify patterns, make predictions, or take actions based on provided data. In essence, machine learning grants computers the ability to